Analysis of the Influence of Brand Image as a Moderating Variable in the Relationship between Influencer Credibility and Electronic Word of Mouth (E-WOM) on Purchase Decisions in Online Marketplaces - Tjiptojuwono, Eko; Dianova, Agustina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of brand image as a moderating variable in the relationship between influencer credibility and electronic word of mouth (E-WOM) on purchase decisions in online marketplaces. The increasing influence of social media and digital marketplaces highlights the importance of understanding how source credibility and brand perception affect consumer purchasing behavior. This research employs an explanatory quantitative approach by distributing online questionnaires to 40 active users of online marketplaces. The data were analyzed using Moderated Regression Analysis (MRA) to test both the direct and moderating effects. The results reveal that influencer credibility and E-WOM have a positive and significant impact on purchase decisions. Furthermore, brand image significantly moderates the relationship between these variables and purchase decisions. These findings indicate that a strong brand image enhances the effectiveness of digital promotional messages in shaping consumer purchasing decisions. This study contributes to the development of digital marketing theory by positioning brand image as a moderating variable that plays a crucial role in the interaction between source credibility and consumer behavior. Practically, the results provide strategic implications for companies to build a consistent brand image, select credible influencers, and manage authentic E-WOM to increase purchase decisions in online marketplaces.